The effect of risk factors on cognition in adult cochlear implant candidates with severe to profound hearing loss - Calvino, Miryam; Sánchez-Cuadrado, Isabel; Gavilán, Javier; Lassaletta, Luis (Frontiers in Psychology, 2022)
Hearing loss has been identified as a major modifiable risk factors for dementia. Adult candidates for cochlear implantation (CI) represent a population at risk of hearing loss-associated cognitive decline. This study investigated the impact of demographics, habits, and medical and psychological risk factors on cognition within such a cohort. Data from 34 consecutive adults with postlingual deafness scheduled for CI were analyzed. Pure tone audiometry(PTA4) and Speech Discrimination Score(SDS) were recorded. The Repeatable Battery for Assessment of Neuropsychological Status for Hearing impaired individuals (RBANS-H) was used to measure cognition. Demographics (sex, age, years of education), habits (smoking, alcohol intake, physical inactivity), and medical factors (hypertension, diabetes, traumatic brain injury) were evaluated. Depression was measured using the Hospital Anxiety and Depression Scale (HADS), and social inhibition with the Type D questionnaire (DS14). All participants(mean age 62±15y) suffered from severe to profound hearing loss(PTA4:129±60dB; SDS:14±24%). The mean RBANS-H total score was 83±16. Participants reported a mean of years of formal education of 12±5y. The prevalence of habits and medical risk factors was:physical inactivity(29%), body mass index >30(28%), traumatic brain injury(25%), hypertension(24%), heavy alcohol consumption(13%), smoking(13%), and diabetes(0%). Regarding psychological factors, the mean scores of social inhibition and depression were 10±6 and 6±5, respectively. The number of years of education was significantly correlated with the RBANS-H total score (p<0.001), and with the domains “Immediate memory”(p=0.003), “Visuospatial/constructional” (p<0.001), and “Attention”(p<0.001). The mean RBANS-H total score in participants who had university studies or higher level(12/34) was 97±9, with the remaining participants reporting a mean score of 75±15. Men performed better in the “Visuospatial/constructional”(p=0.008). Physical inactivity was associated with lower scores in the “Delayed memory”(p=0.031); and hypertension correlated with lower RBANS-H total scores (p=0.025) and “Attention”(p=0.006). Depression and social inhibition were negatively correlated with RBANS-H total score and with the “Immediate memory”, “Visuospatial/constructional”, and “Attention”(all p<0.05). In adults with late-onset deafness scheduled to CI, educational level has a significant influence. Additionally, sex, physical inactivity, hypertension, and psychological traits of social inhibition and depression may also impact cognitive status. Long-term studies with more participants would enable us better understand the effects different risk factors on cognitive status